2005
DOI: 10.1136/gut.2004.047563
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in the treatment of cancer cachexia: a randomised placebo controlled trial

Abstract: Background: Proinflammatory cytokines, especially tumour necrosis factor a (TNF-a), play a prominent role in the pathogenesis of cancer cachexia. Thalidomide, which is an inhibitor of TNF-a synthesis, may represent a novel and rational approach to the treatment of cancer cachexia. Aims: To assess the safety and efficacy of thalidomide in attenuating weight loss in patients with cachexia secondary to advanced pancreatic cancer. Methods: Fifty patients with advanced pancreatic cancer who had lost at least 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
163
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(173 citation statements)
references
References 37 publications
4
163
0
6
Order By: Relevance
“…We agree with Wilkes and Freeman, which the study by Gordon et al 4 suggests, that in this context thalidomide has promising features.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…We agree with Wilkes and Freeman, which the study by Gordon et al 4 suggests, that in this context thalidomide has promising features.…”
supporting
confidence: 50%
“…The study by Gordon et al 4 demonstrates a potential benefit of thalidomide in a small group (N ¼ 17 at 4 weeks and N ¼ 12 at 8 weeks) of patients with end-stage pancreatic cancer on preservation of body weight and lean body mass, but no clear benefit with regard to quality of life was observed. 4 The potential mechanism by which thalidomide may work includes: inhibition of angiogenesis (anticancer effect), decrease in adhesion molecules, inhibition of cyclo-oxygenase 2, modulation of NFjB action and inhibition of proinflammatory mediators, especially tumour necrosis factor (TNF)-a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However compared with prior studies, our sample size was smaller, we had a high rate of the attrition, and noncompliance rates were higher. 7,14 We found that there was no significant difference in the toxicity related to the treatment with thalidomide as compared with placebo (Table 4). These results were similar to those of prior studies by our team and of studies by others on the safety of low-dose thalidomide.…”
Section: Discussionmentioning
confidence: 80%
“…These results were similar to those of prior studies by our team and of studies by others on the safety of low-dose thalidomide. 7,8,[13][14][15] Further studies are needed on the use of thalidomide for ACS based on preliminary safety and efficacy data from prior studies. It is possible that the drug may be of particular utility in the developing world due to its low cost and easy access.…”
Section: Discussionmentioning
confidence: 99%